Of Jks-1 Malein Sopolymer Additive On The Physical And Mechanical Properties Of Cement Binder (Eurasian Journal of Engineering and Technology, 2024)
The article presents the results obtained in determining the physical and mechanical properties of the cement composition with JKS-1 malien copolymer chemical additive.